Pemetaan Riset Asesmen dan Evaluasi Pembelajaran Kimia serta Pengembangan Instrumen HOTS dan Asesmen Autentik Tinjauan Bibliometrik - Luki Yunita; Salamah Agung; Sharla Sabilla; Azahra Rizki Aulia (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
Research on assessment and evaluation in chemistry education continues to grow in response to the increasing demand for comprehensive assessment systems. This study aims to analyze the development, trends, and research structure of assessment and evaluation in chemistry education using a bibliometric approach. Data were collected from the Google Scholar database using keywords related to chemistry learning assessment, chemistry learning evaluation, learning outcome assessment in Kurikulum merdeka, Higher Order Thinking Skills (HOTS), and authentic assessment. A total of 80 articles published between 2022 and 2026 were analyzed using VOSviewer. The results showed that the publications received 1,949 citations, with an average of 24.36 citations per article, an h-index of 7, and a g-index of 44. Publication trends peaked in 2024 before declining in 2025–2026. Network visualization identified HOTS as the central keyword linked to learning, formative assessment, summative assessment, diagnostic assessment, and Problem-Based Learning (PBL). Overlay visualization revealed a shift toward deep learning and diverse assessment approaches, while density visualization indicated that HOTS, learning, formative assessment, and summative assessment were the dominant research topics. These findings provide an overview of research trends in chemistry education assessment and evaluation and may serve as a reference for future studies.